Navigating Rubber Band Syndrome in Dogs: A Report of Three Cases - Reddy, Puli Vishnu Vardhan; Raj, Pushkin; Simon, Shiju; Sindhu, Ramasamy; Ratnam, Thenmozhi (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The presence of strangulating foreign bodies within the  limbs of dogs is a matter of considerable veterinary  concern due to the potential for various complications,  including constriction, compromised blood flow, and damage  to musculoskeletal and neurovascular structures (John et al.,  2019). A specific manifestation of this issue is rubber band  syndrome or circumferential strangulating foreign bodies,  characterized by the presence of encircling external materials  around distal limbs (Arora and Agarwal, 2004; Aggarwal et al.,  2010). Notably, this phenomenon is predominantly reported  in India, where ceremonial or religious bands, often worn for  both aesthetic and ritualistic purposes, are frequently tied  around wrists and ankles. Unfortunately, these bands are  inadvertently forgotten, resulting in adverse consequences  (Baddula et al., 2021).
Keywords: concern; constriction; musculoskeletal; characterized; strangulating